On the eve the jews of europe before the second world war - Wasserstein, Bernard (Simon & Schuster,Inc., 2012)
Presents a disturbing interpretation of the collapse of European Jewish civilization even before the Nazi onslaught. Ranging from Vilna ('Jerusalem of Lithuania') to Salonica with its Judeo-Espanol-speaking stevedores and singers, and beyond, this book focuses squarely on the Jews themselves rather than their persecutors